KKN Tematik: Membangun Kesadaran Pencegahan dan Pengendalian Penyakit Demam Berdarah Dengue (DBD) di Desa Jeruju Besar: KKN Tematik: Building Awareness to The Prevention and Control of Dengue Hemorrhagic Fever (DHF) in Jeruju Besar Village - Ropiqa, Meri; Wijianto, Bambang; Angellica, Grecya; Yanastya, Salsa Yoana; Putri, Alifa Rapaella Fadia Tito (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Dengue hemorrhagic fever (DHF) is caused by the bite of the female Aedes aegypti mosquito. Dengue hemorrhagic fever cases that occurred in Kubu Raya have reached 1,061 cases with 4 deaths, as of November 22 2023. The importance of preventing and controlling dengue fever needs to be done to reduce the increasing number of dengue fever cases that occur so that this problem is raised as KKN theme in Jeruju Besar Village. The KKN implementation was carried out in Jeruju Besar Village with a program to prevent and control dengue hemorrhagic fever which included socialization, training in making larvicide and wall magazine, also providing larvicide products, posters and platelet-increasing food. The results of evaluation show that there was an influence of the socialization carried out on increasing knowledge and understanding regarding dengue prevention and control among village residents from an average value of 59.24 to 87.83 and among elementary school students from an average value of 55.09 to 82 .61 which is supported by the Paired Sample T Test. The result of questionnaires also showed a good level of satisfaction from residents, where 82.61% felt that the were useful. Overall, the program implemented went well according to plan and received a very good response so that it was able to increase understanding and knowledge, also increase awareness in preventing and controlling the spread of dengue hemorrhagic fever among the residents of Jeruju Besar Village.